Probing deposition temperature effects and computational analysis of DC-sputtered tungsten (W) thin films for CZTS based solar cells - M.I. Hossain (22303861) (2025)
Tungsten (W) thin films were deposited onto pre-cleaned soda-lime glass substrates at temperatures ranging from room temperature to 400 °C using DC magnetron sputtering. This deposition process was conducted to investigate how varying substrate temperatures affect the films' crystallographic, morphological, and electrical characteristics. The films' crystallographic structure was examined through X-ray diffraction (XRD), while the surface morphology was analyzed using Field Emission Scanning Electron Microscopy (FESEM). Additionally, the electrical properties of the films were assessed via Hall Effect measurements to better understand the influence of substrate temperature on their conductivity and carrier mobility. XRD analysis revealed two diffraction peaks corresponding to the (200) and (210) planes of the cubic b-W phase, located at around 35° and 39°, respectively. An increase in peak intensities was observed as the substrate temperature rose up to 200 °C. The observed shift of peak positions towards higher 2θ values with increasing temperature suggests strain relaxation within the W lattice, as evidenced by a reduction in lattice parameters. FESEM images confirm the microstructural dependency on the substrate temperature. Electrical measurements were conducted, and the measured carrier concentration was around 10¹⁴ cm⁻³, increasing with temperature up to 200 °C before decreasing again. Films deposited at higher temperatures exhibited lower resistivity. Later, a novel heterojunction solar cell design incorporating a p-type CZTS absorber layer is analyzed in terms of absorber layer thickness with tungsten metal contact where the metal contact thickness was kept at 100 nm. These results suggest that the W films have strong potential for use in CZTS-based thin film solar cells. Other Information Published in: Next Research License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.nexres.2025.100163